PERUBAHAN KATA “TIADA” DALAM TIGA KARYA SASTRA: BUSTAN AS-SALATIN (1640), HIKAYAT SIAK (1855), DAN KETIKA CINTA BERTASBIH 2 (2009) - Suswandi, Irwan (Jurnal KATA, 2018)
In the reality, language will always change. One of examples is the change of language that used in Malay literature manuscripts. In this research, researcher analyzed the language change of “tiada” word that occured in three different periods of manuscript. The approaches used in this research were semantic, morphologic, and syntactic approach. In analyzing those approaches, researcher used semantic restrictions from Verhaar (1992), morphologic restriction from Chaer (1994), and syntactic restriction from Kridalaksana (1999). The researcher used descriptive analysis method. The data used in this research were three literary manuscripts with a span of two centuries, Bustan as-Salatin (1640), Hikayat Siak (1855), and Ketika Cinta Bertasbih 2 (2009).  The analysis of this research resulted information that containing “tiada” which covered all of the language aspects; semantic, morphologic, and syntactic. From the analysis, the researcher got the conclusions that “tiada” in the manuscript at the beginning period had more varied form than the manuscript in the two periods thereafter. Then, in the final period, there were changes of “tiada” that undergoes semantic and morphologic changes from the text of the two previous periods.Dalam kenyataannya, bahasa akan selalu berubah. Salah satu contohnya adalah perubahan bahasa yang digunakan dalam naskah sastra Melayu. Dalam penelitian ini, peneliti menganalisis perubahan bahasa kata "tiada" yang terjadi dalam tiga periode naskah yang berbeda. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan semantik, morfologi, dan sintaksis. Dalam menganalisis pendekatan tersebut, peneliti menggunakan batasan semantik dari Verhaar (1992), pembatasan morfologis dari Chaer (1994), dan pembatasan sintaksis dari Kridalaksana (1999). Peneliti menggunakan metode analisis deskriptif. Data yang digunakan dalam penelitian ini adalah tiga naskah sastra dengan rentang waktu dua abad, Bustan as-Salatin (1640), Hikayat Siak (1855), dan Ketika Cinta Bertasbih 2 (2009). Analisis penelitian ini menghasilkan informasi yang mengandung "tiada" yang mencakup semua aspek bahasa; semantik, morfologis, dan sintaksis. Dari hasil analisis, peneliti mendapatkan kesimpulan bahwa "tiada" dalam naskah pada periode awal memiliki bentuk yang lebih bervariasi daripada manuskrip dalam dua periode sesudahnya. Kemudian, pada periode akhir, terjadi perubahan "tiada" yang mengalami perubahan semantik dan morfologis dari teks dua periode sebelumnya.